2011
DOI: 10.1111/j.1442-2050.2010.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Unsedated transnasal ultrathin esophagogastroduodenoscopy may provide betterdiagnostic performance in gastroesophageal reflux disease

Abstract: Transnasal ultrathin esophagogastroduodenoscopy (N-EGD) with less gagging reflexes under non-sedation is likely suitable for the diagnosis of gastroesophageal reflux disease (GERD), however, N-EGD might have drawbacks, including its low image resolution. Limited information is available regarding the diagnosability of N-EGD for GERD. We compared the utility and gagging reflexes of three different endoscopies, including N-EGD, ultrathin transoral EGD (UTO-EGD) and conventional oral EGD (CO-EGD), in the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 21 publications
1
21
0
2
Order By: Relevance
“…Diagnostic yield was similar in both groups (Table ). This is in agreement with current literature for the detection of Barrett's oesophagus (BO), gastric cancer, and gastro‐oesophageal reflux associated diseases . Other studies, although consisting of small numbers, found that ultrathin endoscopes had similar diagnostic abilities .…”
Section: Discussionsupporting
confidence: 92%
“…Diagnostic yield was similar in both groups (Table ). This is in agreement with current literature for the detection of Barrett's oesophagus (BO), gastric cancer, and gastro‐oesophageal reflux associated diseases . Other studies, although consisting of small numbers, found that ultrathin endoscopes had similar diagnostic abilities .…”
Section: Discussionsupporting
confidence: 92%
“…Studies assessing concordance rates between transnasal esophagoscopy and standard endoscopy demonstrate moderate to good agreement in findings between the two techniques. [711]…”
Section: Discussionmentioning
confidence: 99%
“…[616] The sensitivity of detecting esophageal abnormalities with unsedated small-caliber esophagoscopy is comparable to conventional upper endoscopy. [711] Although unsedated transnasal esophagoscopy is well tolerated in cultures less accustomed to conscious sedation,[11, 1720] studies in North America have been limited by small sample sizes and have been performed in specialized populations selected for either esophageal symptoms or Barrett’s esophagus. [9, 10] Moreover, most studies in the U.S. have been limited to selected populations in referral settings.…”
mentioning
confidence: 99%
“…In previous literature, the diagnostic yield had been found to be similar for the detection of Barrett's oesophagus (BO) and gastric cancer 5 44 45. It has been found to have better performance than oral OGD in the diagnosis of GORD-associated diseases in one paper 46. There has been increasing focus recently on the use of TNE as a screening tool especially for BO and early gastric and oesophageal malignancies.…”
Section: Diagnostic Capabilitymentioning
confidence: 99%
“…The majority of these found better patient tolerance rates in the TNE group based on patient tolerance questionnaires 8 18 20 22 33–36. Patients have greater satisfaction and acceptability4 8 9 20 34–36 and are to be more likely to undergo TNE in the future. They also report a significant reduction in gagging20 37 and in some studies discomfort22 34 (see table 1).…”
Section: Patient Tolerability Side Effects and Safetymentioning
confidence: 99%